1885 N.J. Laws 52 - (:unkn) unknown (My University, 1885)
Ch. 44, 2: That it shall not be lawful to sell, hire or loan to any person under the age of fifteen years any gun, pistol, toy pistol, or other fire-arms; or for any person under the age of fifteen years to purchase, barter or exchange any gun, pistol, toy pistol or other fire-arms; nor for any person under the age of fifteen years to carry, fire or use any gun, pistol, toy pistol or other fire-arms, except in the presence of his father or guardian, or for the purpose of military drill in accordance with the rules of a school.
Keywords: POSSESSION - MINORS; TRANSFER - MINORS